2023
DOI: 10.3390/v15030658
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Shift from SARS-CoV-2 Delta to Omicron Sub-Variants within a Dynamic Southern U.S. Borderplex

Abstract: COVID-19, caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), remains an ongoing global health challenge. This study analyzed 3,641 SARS-CoV-2 positive samples from the El Paso, Texas, community and hospitalized patients over 48 weeks from Fall 2021 to Summer 2022. The binational community along the U.S. southern border was predominantly SARS-CoV-2 Delta variant (B.1.617.2) positive for a 5-week period from September 2021 to January 2022 and quickly transitioned to the Omicron variant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…By the fourth week of December 2021, Delta samples only accounted for 19.0 % during this week and then dropped to undetectable levels in the third week of January 2022. These results are consistent with those observed in other university settings, as well as overall patterns recorded both nationally and across the globe [20, 36–38, 67, 68], although studies investigating this particular replacement are limited in number.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By the fourth week of December 2021, Delta samples only accounted for 19.0 % during this week and then dropped to undetectable levels in the third week of January 2022. These results are consistent with those observed in other university settings, as well as overall patterns recorded both nationally and across the globe [20, 36–38, 67, 68], although studies investigating this particular replacement are limited in number.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, given the importance of higher education in society and the need to maintain confidence in the safety of students, studying the dynamics of infectious disease in these institutions has been of special interest [19–27]. There have been multiple previous works which have investigated various aspects of SARS-CoV-2 dynamics in university settings since the pandemic began, ranging from genomic epidemiology to modelling studies and routine surveillance [20–24, 26, 28–35]; however, very few studies have explored the transition from Delta to Omicron variants [36–39], let alone in university populations [40].…”
Section: Introductionmentioning
confidence: 99%
“…These findings resonate with findings from Puerto Rico, where the BA1 variant emerged replacing Delta as the dominant variant in December 2021, which was followed by increased transmission and a dynamic landscape of Omicron sublineage infections in the population [ 80 ]. Further studies have reported increased transmission and infection attributable to the emergence of the Omicron variant after the replacement of Delta in England, Finland and the United States of America [ 81 , 82 , 83 ]. Further, the spread of the Omicron variant in Eastern Province exhibited similarities to its spread in South Africa and Malawi [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%